Ruminally-Protected Lysine (SafeGain) Improves Performance of Growing Beef Cattle - V. A. Veloso; C. L. Van Bibber-Krueger; J. S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2016)
Lysine frequently is cited as the first-limiting amino acid for cattle diets. Synthetic lysine, while routinely added to pig diets, is ineffective in fulfilling lysine requirements of cattle due to extensive degradation by microbes within the rumen. Lysine can be encapsulated with compounds, such as saturated fats, that minimize degradation by ruminal microbes, thereby assuring that a greater proportion of the amino acid is available for absorption post-ruminally. The purpose of this experiment was to measure the impact of SafeGain (H.J. Baker & Bro. Inc., Little Rock, AR), an encapsulated form of lysine sulfate, on rate of gain and feed efficiency in backgrounding cattle.
Keywords: lysine; encapsulation; backgrounding